2021
DOI: 10.3390/ijgi10010025
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of People’s Privacy Concerns, Perceptions of Social Benefits, and Acceptance of COVID-19 Mitigation Measures That Harness Location Information: A Comparative Study of the U.S. and South Korea

Abstract: This paper examines people’s privacy concerns, perceptions of social benefits, and acceptance of various COVID-19 control measures that harness location information using data collected through an online survey in the U.S. and South Korea. The results indicate that people have higher privacy concerns for methods that use more sensitive and private information. The results also reveal that people’s perceptions of social benefits are low when their privacy concerns are high, indicating a trade-off relationship b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 41 publications
3
34
0
3
Order By: Relevance
“…Researchers have examined people's privacy concerns and acceptance of various COVID-19 control measures. For example, a survey of U.S. and Korean individuals by Kim and Kwan [ 23 ] focused on the geographic location and context in understanding privacy concerns surrounding COVID-19 policies and found that due to the collectivist nature of the Korean society, vaccination passports have a comparatively greater acceptance there. It can thus be deduced that other collectivists cultures in Asia and Africa may have a greater acceptability of COVID-19 passports than Europe and North America.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers have examined people's privacy concerns and acceptance of various COVID-19 control measures. For example, a survey of U.S. and Korean individuals by Kim and Kwan [ 23 ] focused on the geographic location and context in understanding privacy concerns surrounding COVID-19 policies and found that due to the collectivist nature of the Korean society, vaccination passports have a comparatively greater acceptance there. It can thus be deduced that other collectivists cultures in Asia and Africa may have a greater acceptability of COVID-19 passports than Europe and North America.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sihombing et al [27] discussed the privacy protection methods adopted by nine different countries. In addition, other researchers have presented reviews about the country-specific privacy-protection methods used in the COVID-19 era [28]- [30]. Furthermore, some surveys have been published on the quantification of privacy risks [31], as to the nature of digital solutions (e.g., centralized or decentralized) [32], on the (non)acceptability of digital apps [33], on emerging technologies' privacy issues in COVID-19 context [34], about privacy controversies towards aggressive use of information technology amid the pandemic [35], and on healthcare privacy challenges in COVID-19 period [36].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, data sharing has become critical as research reproducibility has received growing attention in the scientific community (Alter & Gonzalez, 2018; Kedron, Li, Fotheringham, & Goodchild, 2021; McNutt, 2014). In the field of geographic information science (GIScience) and public health, however, sharing data can often lead to serious geoprivacy violation because data often contain people's confidential locational information, such as home locations and daily GPS trajectories (Haley et al., 2016; Kim & Kwan, 2021a; Kim, Kwan, Levenstein, & Richardson, 2021; Kounadi & Leitner, 2014; Kwan, Casas, & Schmitz, 2004; Richardson, Kwan, Alter, & McKendry, 2015). To protect people's geoprivacy when sharing data, researchers have developed and applied various geomasking techniques, which deliberately introduce spatial errors to location data to reduce disclosure risks (Armstrong, Rushton, & Zimmerman, 1999; Curtis, Mills, Agustin, & Cocknurn, 2011; Zandbergen, 2014).…”
Section: Introductionmentioning
confidence: 99%